Managing a massacre savagery, civility, and gender in Moro province in the wake of Bud Dajo - Hawkins, Michael C. (Ateneo de Manila University, 2011)
This article examines the delicate ideological maneuverings that shaped American colonial constructions of savagery, civility, and gender in the wake of the Bud Dajo massacre in the Philippines's Muslim south in 1906.
Includes bibliographic references (p. 103-105).
Keywords: Philippines -- History -- Philippine American war, 1899-1902.; Massacres -- Philippines (Mindanao).